Molecular evidence for a recent demographic expansion in the puma (Puma concolor) (Mammalia, Felidae) - Eunice M. Matte; Camila S. Castilho; Renata A. Miotto; Denis A. Sana; Warren E. Johnson; Stephen J. O'Brien; Thales R. O. de Freitas; Eduardo Eizirik (Genetics and Molecular Biology, 2013)
The puma is an iconic predator that ranges throughout the Americas, occupying diverse habitats. Previous phylogeographic analyses have revealed that it exhibits moderate levels of genetic structure across its range, with few of the classically recognized subspecies being supported as distinct demographic units. Moreover, most of the species' molecular diversity was found to be in South America. To further investigate the phylogeographic structure and demographic history of pumas we analyzed mtDNA sequences from 186 individuals sampled throughout their range, with emphasis on South America. Our objectives were to refine the phylogeographic assessment within South America and to investigate the demographic history of pumas using a coalescent approach. Our results extend previous phylogeographic findings, reassessing the delimitation of historical population units in South America and demonstrating that this species experienced a considerable demographic expansion in the Holocene, ca. 8,000 years ago. Our analyses indicate that this expansion occurred in South America, prior to the hypothesized re-colonization of North America, which was therefore inferred to be even more recent. The estimated demographic history supports the interpretation that pumas suffered a severe demographic decline in the Late Pleistocene throughout their distribution, followed by population expansion and re-colonization of the range, initiating from South America.